Surface modification of PLA scaffold using radio frequency (RF) nitrogen plasma in tissue engineering application. (19th March 2020) - Mohsenimehr, Soad; Khani, Mohammad Reza; Fani, Nesa; Baghaban Eslaminejad, Mohammad Reza; Shokri, Babak; Ghassami, Amirreza
Abstract: In this study, two models of flat film and three-dimensional porous structure made by 3D printing (scaffolding) of poly lactic acid polymer (PLA) were processed by radio frequency (RF; 13.56 MHz) low-pressure nitrogen, nitrogen/oxygen and nitrogen/hydrogen plasma to improve surface properties requested in tissue engineering. Samples were treated at different RF power (80–150 w) and time processing was 90 s. Optical emission spectroscopy was used to identify the species in plasma. A significant change in hydrophilicity and surface energy measured by contact angle was observed. Aging effect on the wettability of PLA films at two different temperatures was examined. The result showed that the samples, kept at low temperature, have not changed significantly. Morphology and surface roughness were studied by Atomic force microscopy. Chemical components at the surface were investigated by x-ray photoelectron spectroscopy (XPS). Mechanical and thermal effect on the 3D scaffold PLA were carried out by tension test and thermogravimetric analysis respectively to indicate the effects of RF plasma treatment on the samples. The structural order, interconnectivity, and scale of the scaffold holes have been recorded by an optical microscope. Surface treatment by plasma increased biocompatibility of PLA samples without any toxicity. Cell adhesion on scaffolds was approved through MTT and scanning electron microscope (SEM) analysis. MTT essay show there was significant different between N2 /O2 (1:1) group than control sample. Plasma surface treatment is a convenient method to reach a perfect substrate with desired hydrophilicity for attaching cells.